2020
DOI: 10.1016/j.omtm.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nanovesicles from Orange Juice to Reverse Diet-Induced Gut Modifications in Diet-Induced Obese Mice

Abstract: We have determined whether orange juice-derived nanovesicles (ONVs) could be used for the treatment of obesity-associated intestinal complications. ONVs were characterized by lipidomic, metabolomic, electron microscopy. In vitro, intestinal barriers (IBs = Caco-2+HT-29-MTX) were treated with ONVs and co-cultured with adipocytes to monitor IB fat release. In vivo, obesity was induced with a high-fat, high-sucrose diet (HFHSD mice) for 12 weeks. Then, half of HFHSD mice were gavaged with ONVs. One-month ONV trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 61 publications
2
89
0
Order By: Relevance
“…Current research regarding plant nanovesicles deals with general properties [ 3 , 12 , 13 , 14 ], host-versus-pathogen-interactions [ 8 , 11 , 15 , 16 , 17 ] and health-beneficial effects [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Another approach to use the advantageous properties of plant nanovesicles can be to foster the use of these small non-coding RNA (sRNA)-containing vehicles as bio-compatible and sustainable plant protection agents [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Current research regarding plant nanovesicles deals with general properties [ 3 , 12 , 13 , 14 ], host-versus-pathogen-interactions [ 8 , 11 , 15 , 16 , 17 ] and health-beneficial effects [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Another approach to use the advantageous properties of plant nanovesicles can be to foster the use of these small non-coding RNA (sRNA)-containing vehicles as bio-compatible and sustainable plant protection agents [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although we have already learned a lot about properties and effects of vesicle subtypes isolated from distinct plant materials, we still neither know for sure how EVs pass through the apoplastic space or cell walls, nor what their function truly is. Considering the inhibitory effects of plant nanovesicles against pathogenic microorganisms and increased vesicle amounts after fungal infections in plants [ 8 , 10 , 11 , 17 , 25 ] together with the diversity of plant nanovesicle lipids [ 17 , 18 , 24 , 26 ], one can assume that plant cells produce EVs in order to control the growth of pathogenic microorganisms in case those try to invade the plant and also to address distant host cells, e.g., to improve their immune response. Taking into account that some pests mainly infect particular plants or plant families, it is plausible to imagine that not only the vesicle’s cargo is tuned by the host but also the envelope, to fight such pests as effectively as possible.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, supplementation with EV from external sources might also contribute to restoring obesity-related WAT function and thereby modulate AdEV biological functions. For instance, we demonstrated that nanovesicles from orange juice could reverse high-fat-diet-induced gut modifications (e.g., length of villi and immune response) in diet-induced obese mice [ 96 ]. Additional investigations will be required to envisage diet and/or supplements as a strategy to modulate AdEV content in order to counteract their deleterious biological effects.…”
Section: Therapeutic Strategies To Decrease Ad Ev Deleterious Effementioning
confidence: 99%